Exploiting potential of medicinal plants in arid region - Janakiram, T; Maniwell, Maniwell (Indian Horticulture, 2019)
Though number of medicinal plants are in cultivation in Rajasthan, only few medicinal plants like Isabgol, Ashwagandha, Sonamukhi, Opium Poppy, Safed musli and Mehndi could get a sizeable area. As far as the growth of area, production and yield of medicinal and aromatic crops in various districts of Rajasthan is concerned, it may be noted that Jalore district occupied the first position in terms of area under medicinal and aromatic crops. During 2015- 16, area under cultivation of MAPs in Rajasthan was 370 thousand ha as against the total area of 634 thousand of all India average with the production of 190 thousand MT as compared to 1030.85 thousand tonnes of the country. The annual growth rate of area under medicinal and aromatic crops was highest (66.6%) in Rajsamand district during the last decade followed by Hanumangarh (50.8%) and 37.7% in Jaipur district. However, the annual growth rate of production of medicinal and aromatic crops was highest in Baran (72.6%), followed by Udaipur (48.8%) and Jhalawar district (20.9%). The annual growth rate of area and yield of medicinal and aromatic crops was lowest in Bharatpur (–96.1%) and Sri Ganganagar (–33.8%) districts, respectively.